Asia-Pacific Conference on Environmental Electromagnetics, 2003. CEEM 2003. Proceedings. 2003
DOI: 10.1109/ceem.2003.238406
|View full text |Cite
|
Sign up to set email alerts
|

Observation of sprites over the Sea of Japan and conditions for lightning-induced sprites in winter

Abstract: We have succeeded in observing sprites for winter lightning in the Hokuriku area (Japan Sea side) of Japan in the winter of 2001/2002. The optical results on three days are compared with the corresponding characteristics of parent (causative) lightning with particular attention to the significant diferences between Hokuriku winter lightning and the more widely studied continental lightning. Despite significant differences with Hokuriku winter lightning. We have found nearly the same sprite properties as alread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(95 citation statements)
references
References 0 publications
8
87
0
Order By: Relevance
“…Several images of column-form sprites [Hayakawa et al, 2004] were captured at 10:37:59.36 UT on 11 January 2005. In addition, the sprite-parent lightning discharges and their thunderclouds were observed with the weather radar, the SAFIR and the field mill network.…”
Section: Observational Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several images of column-form sprites [Hayakawa et al, 2004] were captured at 10:37:59.36 UT on 11 January 2005. In addition, the sprite-parent lightning discharges and their thunderclouds were observed with the weather radar, the SAFIR and the field mill network.…”
Section: Observational Resultsmentioning
confidence: 99%
“…Eleven of these fifteen events are found to exhibit similar characteristics to those for one particular event presented in this paper. Hayakawa et al [2004] have shown that self-organization may be essential for the generation of sprite parent thundercloud systems. This conclusion is further supported by this report based on combined use of different observations including weather radar, SAFIR, and the GOES-9 satellite.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The carrot type sprite contains diffuse tops and lower tendrils extending down to altitudes of 30-40 km, while the columniform sprite has a very fine spatial structure as compared with the "carrot" sprite (e.g. Hayakawa et al, 2004;Wescott et al, 1998). The faint red glow diffusion region lies in the altitude range 85 to 90 km, while the brightest region occurs in the 65-85 km altitude range.…”
Section: Spritesmentioning
confidence: 99%